Proinflammatory cytokines and procalcitonin in children with acute pyelonephritis - Gürgöze, MK; Akarsu, S; Yilmaz, E; Gödekmerdan, A; Akça, Z; Çiftçi, I; Aygün, AD (Springer, 2005)
This prospective study, performed in 76 children with a urinary tract infection (UTI), evaluates the diagnostic value of procalcitonin (PCT) and proinflammatory cytokines (IL-1 beta, IL-6 and TNF-alpha) in children with acute pyelonephritis documented by dimercaptosuccinic acid scintigraphy (DMSA). Renal parenchymal involvement was assessed by Tc-99m-DMSA scintigraphy within 7 days of admission. The diagnosis of acute pyelonephritis was confirmed only in patients with reversible lesions on scintigraphy. According to DMSA scan results, patients were divided into two groups, lower UTI or acute pyelonephritis. In acute pyelonephritis, serum PCT level was found to be significantly higher than it is in the lower UTI (p < 0.001). Also, significantly higher serum proinflammatory cytokines (IL-1 beta, IL-6 and TNF-alpha) levels were detected in those with acute pyelonephritis than those with lower UTI (p < 0.001). We conclude that both serum PCT and proinflammatory cytokine levels may be used as accurate markers for diagnosis of acute pyelonephritis.
Keywords: acute phase reactant; acute pyelonephritis; children; procalcitonin; proinflammatory cytokines